Exploring Intersemiotic Translation Models: A Case Study of Ang Lee’s Films - Loukia Kostopoulou (Syn-Thèses, 2024)
Review of the book Exploring Intersemiotic Translation Models: A Case Study of Ang Lee’s Films by Haoxuan Zhang, Routledge Advances in Translation and Interpreting Studies, New York London, Routledge, 2023, 222 pages, ISBN 9781032395326 (1st edition), Hardback £130.00, eBook £29.24